Public Health Academic Ranking (PHAR) 2025: A Global Perspective - Elsa Gaillard; Konstantina Parsopoulou; Sara Mazzetti; Zoe Sangalli; Klaus Schönenberger; Nicolas Ray; Antoine Flahault (Standards, 2026)
Objectives: To establish a global academic ranking of Schools of Public Health based on bibliometric data. Methods: Data were extracted and analyzed using InCites Benchmarking and Analytics™ and the Web of Science™ Core Collection database. Bibliometric data were collected on a selection of 145 Schools of Public Health from all continents between June and September 2025. Ten research indicators were included for the period 2019–2023. Both global and continental rankings were established. Results: The leading institutions were the Harvard T.H. Chan School of Public Health in North America, also ranked first globally; the London School of Hygiene & Tropical Medicine in Europe; the Department of Public Health at the National Autonomous University of Mexico in Latin America; the Saw Swee Hock School of Public Health in Asia; the School of Public Health at the University of Cape Town in Africa; and the School of Public Health and Preventive Medicine at Monash University in Oceania. Conclusions: PHAR 2025 provides the first global bibliometric ranking of a selection of 145 Schools of Public Health. It is a measure of research activity and bibliometric impact, rather than an assessment of the overall quality or public health contribution of each school.